Psychiatric expert testimony : emerging applications - Weiss, Kenneth J.; Watson, Clarence (Oxford University Press, 2014)
This is a resource for practitioners intending to introduce cutting-edge science into analyses of mental state, in criminal and civil proceedings. It provides a practical treatment of the science behind human development and the uses of technology as they enter the courtroom.